Natural variations in small RNA origin loci generate circuit diversity underlying temperature acclimation in Caenorhabditis elegans - Misaki Okahata; Taichiro Iki; Sawako Yoshina; Yohei Minakuchi; Yukina Mori; Natsumi Sawada; Toru Miura; Toshie Kai; Atsushi Toyoda; Shohei Mitani; Akane Ohta; Atsushi Kuhara (Proceedings of the National Academy of Sciences, 2026)
Individuals respond differently to environmental cues because of inherent variations in genome sequences. This study demonstrates that natural variation in small RNA (sRNA) within embryos epigenetically shapes adaptive neural circuits underlying diverse animal temperature acclimation. We performed comparative genome profiling of Caenorhabditis elegans variants with differential temperature acclimation and identified smrn-1 , a member of a novel gene family predicted to be conserved within nematode genomes. Unexpectedly, determination of full-length smrn-1 sequence by long-read sequencing revealed 1791 orthologues present in human genome. smrn-1 was among the most abundant sRNA-accumulating genes downstream of the helicase ERI-6/7 functioning in embryos. smrn-1 -derived sRNAs were loaded onto the Argonaute protein HRDE-1, thereby regulating axonogenesis of O 2 -sensing BAG neurons through upregulation of an axonogenesis regulator protein. O 2 information from BAG influences the thermal responsiveness of temperature-sensing neurons, resulting in individual diversity in temperature acclimation. Thus, natural variation in embryonic sRNA epigenetically forms adaptive neural circuits associated with diverse temperature acclimation. We propose that accumulation of gene polymorphisms producing epigenetic regulators during nematode evolution generates adaptive neural circuits for temperature acclimation.